Quantity surveyors in green construction: threats and challenges - Che Haron, Roziha; Mat Rawi, Azya (UTM Razak School, 2014)
The wave of sustainable construction has created changes within the complex environment of the construction industry. This globalization has shifted the traditional way into a new paradigm of sustainable practice and resulted in a growing demand in green construction and sustainable development. Nevertheless, since the understanding of sustainable construction in Malaysia is still in infant phase, construction players such as quantity surveyors are still struggling to respond to the green demand in order to safeguard the relevancy and efficiency of the profession. Thus, the aim of this paper is to study the practice of quantity surveyors in sustainable construction by focusing on facing threats and challenges. Two objectives have been constructed which are to identify the current level of green knowledge and understanding among quantity surveyors and to identify the threats and challenges in managing sustainable projects. A mixed method of data collection is carried out within Selangor, where questionnaire survey is distributed and several interview sessions are conducted. Finding shows that quantity surveyors are having high environmental awareness and green consciousness, but lower knowledge and understanding in the concept and implementation of green practice. They are facing highest challenges due to lack of cost information regarding green material, equipment and labor, and lack of knowledge on green technologies. To overcome the challenges are not a one-side effort. It is a cooperative responsibility of all stakeholders within the industries since most of the challenges are interrelated with various factors and forces.